KEDEKATAN STRATEGIS INDONESIA DALAM RIVALITAS AS–CINA PASCA COVID-19 - Anwar, Ahmad; Akta Padma Eldo, Dwian Hartomi (Universitas Jenderal Ahmad Yani, 2025)
This study develops a Proximity Index to measure Indonesia's proximity to the United States and China, particularly after the COVID-19 pandemic. The index integrates three dimensions (economic, military, and diplomatic) to operationalize proximity as a multidimensional index. The time-series analysis reveals structural asymmetry: Indonesia's military ties remain consistently anchored to the US; economic dependence leans more toward China; and diplomacy is a fluctuating driver of the index. The study identifies three inflection points (2019, 2022, and 2024) when diplomatic oscillations (the COVID-19 pandemic, Indonesia's G20 presidency, and domestic leadership transition) recalibrate overall proximity. The statistical predictions suggest a gradual shift toward China due to strengthening economic integration. These findings also underscore that Indonesia's foreign policy reflects a rebalancing of its composition, rather than a complete restructuring.